Abordagens multivariadas no estudo da dinâmica de comunidades de macrófitas aquáticas - Pitelli, Robinson Luiz de Campos Machado [UNESP] (2006)
The aquatic weeds are essentially important in water bodies under strong antropic influence, especially in hydropower water reservoirs built-up in highly urbanized regions. In the energy generation system of hydropower company Light Serviços de Eletricidade , the Santana reservoir historically has more problems with aquatic weeds. Aiming to solve these problems the company periodically promotes a mechanical harvesting cleaning up the reservoir, but after some time it is completely re-colonized by the macrophytes and the 4 problems are back. Aiming to understand the macrophytes re-colonization dynamics, fields surveys were done monthly, identifying and quantifying the aquatic weed populations in 91 sampling sites. The weeds quantification was done by means of a colonization scale changing from 0 (no plants) to 4 (high colonization, more than 80% of the sampling site). The evolution of colonization area and the geographic distribution pattern were studied for aquatic weed populations, while diversity and equitability coefficients, several similarity index and multivariate analysis were applied to study the macrophyte communities between sampling times. There was a well defined colonization succession process, characterized by variation in the relative size of the different populations and some seral stages could be established, at least for mechanical harvesting planning and some biotic conditions of the macrophyte community. It was not possible to detect a succession of populations, but a succession of colonization conditions since there were no expressive increments or extinctions of species in the reservoir during the year. The exotic species to the reservoir and with early colonization were the predominant ones in the macrophyte community with special attention to Egeria densa and Brachiaria arrecta. For some species, as Eichhornia crassipes and Myriophyllum aquaticum, the biotic pressures of natural enemies probably had decisive effects on.